KOMPETITIF HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI GERAI SAYUR CIPUTAT - Achmad Afif; Arifman Jaya Hura; Dini Anggraini; Irma Suzita; Novan Danurwino; Sewaka Sewaka (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine, in part or together, the impact of competitive prices and strategic location on purchasing decisions of existing Ciputat Vegetable Outlets. The research method used is associative with a quantitative approach, the research population is consumers, totalling 14,037 (sales data). Based on the Slovin formula, the number of research samples obtained was 99 respondents. The data analysis used a statistical regression test approach. The findings of this study are in the form of information, which shows a positive relationship between purchasing decisions with price and location, both in partial and simultaneous tests. This finding is evidence, consumers set a number of judgments in the decision to buy a product/service, and the most important criteria are about price and location.